Aerodynamic performance of a naca 23012 half wing model with a reverse delta wing type add-on device - Asrar, Waqar; Altaf, Afaq; Omar, Ashraf Ali; Hrairi, Meftah; Thong , Boon Tan (2015)

(untitled)
A six component force balance was used to obtain the aerodynamic performance of a NACA 23012 half wing model with a slender reverse delta type add-on device in landing configuration (slat deflection 15° and flap deflection 20°) at a chord-based Reynolds number of Rec =2.74×105. Reverse delta type add-on devices of three different sizes were tested. It was found that the aerodynamic performance of the half wing model was only slightly affected by the use of a reverse delta type addon device. It was found that the reduction in lift is 4.9% and the increase in drag is 15.2%.